Nepal Stock Exchange Index Movement - Timsina, Dhakaram (Dibyajyoti Journal, 2024)
Due to the features of the stock market and NEPSE index, predicting stock price movements is a challenging task. The nature of NEPSE index volatility makes it challenging for investors to booked profit from stocks. The main issues whether the trends and pattern can identify the movement of NEPSE Index or not? To address this problem, investors need to know accurate patterns of past index and make predictions about future price changes. In this study, The research design based on quantitative methods data has collected for 10 years NEPSE Index, used from January 2014 to December 2023 and technical trading tools such as Diagram and trend chart were used to determine the movement of the NEPSE index. As a result, Bullish market start after completion of long pattern of sideways market and exist 13 to 14 month only and falling towards bearish trend the NEPSE index pattern provides buy signal in March and selling signal in July. while the trader can benefit from it in the very short term, but Past performance is no guarantee of future results.